Field scale estimates of soil carbon stocks on ten heavy textured farms across Ireland. (1st March 2021) - Tuohy, P.; O'Sullivan, L.; Fenton, O.
Abstract: The world's soils store vast amounts (≈2, 500 GT) of Carbon which acts as a vital sink to counterbalance the effects of increasing atmospheric carbon dioxide. There have been fruitful efforts to quantify soil Carbon stocks at national scales, which are required for policy level decisions but lack the high resolution required to support farm specific decisions. It is hypothesised that farm scale evaluations of soils can provide insight that is masked in national scale studies and can allow for spatially explicit management approaches to optimise soil Carbon storage and sequestration, such that it can be prioritized within profitable production systems. The objective of the present study was to estimate Carbon stocks on a range of heavy textured soils at field and farm scale and to quantify Carbon storage relative to national scale estimates. Ten grassland dairy farms (mean area of 52.2 Ha) were surveyed, sampled and classified to determine soil types and quantify soil Carbon stores. The level of Carbon present (mean: 346.0 T/Ha) at these sites was greater than previous averages on such soils quantified at national scale (by a factor of 1.1–3.9 depending on soil type). Furthermore, if Carbon saturation potential was realised, the amount of Carbon stored could be increased by an average of 792.1 T/Ha in each profile (from 346.0 to 1138.1 T/Ha). Current management has fostered the retention of large stores of soil Carbon on such soils/farms which co-exist within highly productive farm systems. As there is a societal demand to retain and enhance soil carbon stores to mitigate climate change, high Carbon soils should be identified and, under appropriate policies, commodified to offer a direct incentive to retain soil Carbon. The value of this resource should be recognised and polices to ensure a spatially explicit approach for soil Carbon management should be adopted. Highlights: Carbon stocks are estimated on farms dominated by poorly/imperfectly drained soils. Estimated stocks are greater than previous estimates carried out at national scale. Synergy exists between farm management, C stores and high productivity. Discrepancies between estimates at different scales show a need for further studies.